Ethical challenges in the treatment of psychotic pregnancy denial - John, Roshen; Tudose, Gabriel; Kuo, Chin; Arth, Gabriella; Wong, Sammi (Frontiers in Psychiatry, 2024)
Background: There is a paucity of literature regarding ethical strategies for treating pregnant people with psychosis. While not uncommon, psychotic pregnancy denial is a psychotic illness in which women have the delusion that they are not pregnant. The authors provide a literature review regarding psychotic pregnancy denial, present an unpublished case and its questions and dilemmas, and offer recommendations for resolving the ethical challenges these cases raise. Case: A 26-year-old, single, unemployed woman of no fixed residence was admitted for suicidal ideation. She had a history of psychosis, had multiple ER visits and at least one previous hospitalization, had minimal contact with psychiatric outpatient clinics, and had been poorly compliant with treatment recommendations. She was discovered to be about 31 weeks pregnant in the emergency room. Ultrasound exams revealed no fetal anomalies. This was the patient's second pregnancy; her previous pregnancy resulted in an abortion. Her sole psychotic symptom was the delusional belief that she was not pregnant. On the rare occasions when the patient acknowledged being pregnant, she requested the termination of pregnancy. Despite intensive pharmacological treatment of her psychosis, the patient continued believing that she was not pregnant and repeatedly said she would not participate in the labor and delivery process. She disagreed with the induction of labor or a cesarean section if needed. The patient developed gestational hypertension, an obstetric indication for delivery. Induction of labor was offered to avoid potentially disastrous outcomes for the pregnant woman and the fetus. Conclusion: Psychotic pregnancy denial is potentially life-threatening. Delivery of the fetus requires carefully weighing risks and benefits and thoroughly considering the ethical framework.Teaching points: Treatment of birthing people with psychotic denial of pregnancy is complex; it requires special clinical and ethical skills to determine the patient's level of decision-making impairment and to find a middle ground between the pregnant person's right to autonomy and the physicians' beneficence-based duties. Using a well-coordinated, interdisciplinary approach and a solid ethical framework, the decision to deliver the fetus while engaging the pregnant person, to the extent possible, in the decision-making process is essential.